"Salt and Pepper" Pontine Infarct. Issue 3 (September 2017) - Lyons, Lance J.; Law, Susan W.; Kubie, John L.
Abstract : Abstract: A paramedian pontine stroke may herald the unique symptom of "salt and pepper" eye pain, in which patients describe the sensation of pepper rubbed into the eye. While localization of the lesion is a common thread among published cases, the mechanism for the sensation of eye pain is still a matter of conjecture. It is important for clinicians to be aware of this unique symptom because strokes rarely present with eye pain and failure to establish this diagnosis might lead to a poor clinical outcome.